Lafoeina longitheca Jaderholm 1904 ... - Soto, Joan J.; Peña, Álvaro L. (Zenodo, 2019)
Lafoeina longitheca Jäderholm, 1904 (Fig. 7a) Material examined. ANT XV/3: 48-77, few hydrothecae, on Halecium pseudodelicatulum Peña Cantero, 2014; ANT XVII/3: 111-5, several hydrothecae, on L. dumosa and O. terranovae, with gonothecae; 111-9, numerous hydrothecae, on O. terranovae, T. longstaffi and polychaete tube; 111-18, numerous hydrothecae, on C. hicksoni, H. interpolatum, O. terranovae, Sc. nana and undeterminate hydrorhiza; ANT XXI/2: PS65/251, numerous hydrothecae, on O. terranovae; PS65/281, several hydrothecae, on B. subrufa and Sy. cumberlandicus. Ecology and distribution. Species reported at depths from five (Stepanjants 1979) to 701 m (Peña Cantero 2014a); present material comes from 62 to 360 m. Pan-Antarctic species (Peña Cantero & Vervoort 2009). ... : Published as part of Soto, Joan J. & Peña, Álvaro L., 2019, Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica), pp. 1-78 in Zootaxa 4570 (1) on page 24, DOI: 10.11646/zootaxa.4570.1.1, http://zenodo.org/record/2608527 ...